New Advances in HIV Entry Inhibitors Development - Rusconi, Stefano; Scozzafava, Andrea; Mastrolorenzo, Antonio; Supuran, Claudiu T. (Current Drug Targets - Infectious Disorders, 2004)
Considerable advances have been made in the last years in the design of derivatives acting as inhibitors of HIV entry and fusion. The discovery of chemokines focused the attention on cellular coreceptors used by the virus for entering within cells, and consequently the various steps of such processes have been characterized in detail. Intense research led to a wide range of effective compounds that are able to inhibit the initial steps of HIV life cycle. All steps in the process of HIV entry into the cell may be targeted by specific compounds that may be developed as novel types of antiretrovirals. Thus, several inhibitors of the gp120 - CD4 interaction have been detected so far (zintevir, FP-21399 and BMS-378806 in clinical trials). Small molecule chemokine receptor antagonists acting as HIV entry inhibitors also were described in the last period, which interact both with the CXCR4 coreceptor (such as AMD3100; AMD3465; ALX40-4C; T22, T134 and T140), or which are antagonist of the CCR5 coreceptor (TAK-779, TAK-220, SCH-C, SCH-D, E913, AK-602, UK- 427857 and NSC 651016 in clinical trials), together with new types of fusion inhibitors possessing the same mechanism of action as enfuvirtide (such as T1249). Recently, a third family of antivirals started to be used clinically (in addition to the reverse transcriptase and protease inhibitors), with the advent of enfuvirtide (T20), the first fusion inhibitor to be approved as an anti-HIV agent. Some of these compounds demonstrated in vitro synergism with other classes of antivirals, offering thus the rationale for their combination in therapies for HIV-infected individuals. Many HIV entry and fusion inhibitors are currently being investigated in controlled clinical trials, and a number of them is bioavailable as oral formulations. This is an essential feature for an extended use of these compounds with the purpose of ameliorating adherence of patients to these medications and preventing the development of drug resistance.
Keywords: fusion inhibitor